Use of 35% hydrogen peroxide in tooth bleaching in different clinical time intervals: how long does sensitivity last, and at what times is it more exacerbated? (Bioscience Journal, 2018)
Tooth color is one of the characteristics that define a smile as attractive, and Dentistry offers tooth whitening as an option for achieving this purpose. However, this therapy is almost always accompanied by an inconvenience: dentin sensitivity. The objective of this study was to analyze two 35% hydrogen peroxide based materials, used in different clinical time intervals to evaluate not only the efficacy of color change, but also how long dentin sensitivity lasts, and at what times is it most exacerbated. A total of 24 volunteers were selected. The maxillary arch was divided at the midline, forming the Right Group (RG) composed of the right maxillary hemi-arch (tooth 11-15) and Left Group (LG) composed of the left maxillary hemi-arch (tooth 21-25). The mandibular arch formed the control group CG. The RG received 35% hydrogen peroxide - Whiteness HP® - FGM Produtos Odontológicos, Joinville, SC, Brazil in three sessions of 45 minutes each ( Material 1) and LG received 35% hydrogen peroxide - Pola Office® - SDI Limited, Bayswater, VIC, Australia in three sessions of 24 minutes each ( Material 2) with an interval of one week between sessions. Color was evaluated visually by means of the Vitapan Classical Scale (Vita Zahnfabrick, Bad Säckingen, BW, Germany) at the beginning and end of each session, and 12 days after the last session. There was no statistically significant difference (p